Emerging Role of Long Non-Coding RNAs in Diabetic Vascular Complications - Tanwar, Vinay Singh; Reddy, Marpadga A.; Natarajan, Rama (Frontiers in Endocrinology, 2021)
Chronic metabolic disorders such as obesity and diabetes are associated with accelerated rates of macrovascular and microvascular complications, which are leading causes of morbidity and mortality worldwide. Further understanding of the underlying molecular mechanisms can aid in the development of novel drug targets and therapies to manage these disorders more effectively. Long noncoding RNAs (lncRNAs) that do not have protein-coding potential are expressed in a tissue- and species-specific manner and regulate diverse biological processes. LncRNAs regulate gene expression in cis or in trans through various mechanisms, including interaction with chromatin-modifying proteins and other regulatory proteins and via posttranscriptional mechanisms, including acting as microRNA sponges or as host genes of microRNAs. Emerging evidence suggests that major pathological factors associated with diabetes such as high glucose, free fatty acids, proinflammatory cytokines, and growth factors can dysregulate lncRNAs in inflammatory, cardiac, vascular and renal cells leading to altered expression of key inflammatory genes and fibrotic genes associated with diabetic vascular complications. Here we review recent reports on lncRNA characterization, functions, and mechanisms of action in diabetic vascular complications and translational approaches to target them. These advances can provide new insights into the lncRNA-dependent actions and mechanisms underlying diabetic vascular complications and uncover novel lncRNA-based biomarkers and therapies to reduce disease burden and mortality.